Relationship Between Cesarean Delivery Rate and Maternal and Neonatal Mortality. Issue 4 (December 2016) - Molina, George; Weiser, Thomas G.; Lipsitz, Stuart R.; Esquivel, Micaela M.; Uribe-Leitz, Tarsicio; Azad, Tej; Shah, Neel; Semrau, Katherine; Berry, William R.; Gawande, Atul A.; Haynes, Alex B.
Abstract : (JAMA 2015;314(21):2263–2270) Cesarean deliveries can be lifesaving for women with obstructed labor and other emergency conditions. As per the World Health Organization (WHO) recommendation, cesarean delivery rates should not exceed 10% to 15% of deliveries. However, actual rates are higher in many countries. The aim of this study was to provide better estimates of the contemporary relationship between national cesarean delivery rates and neonatal and maternal mortality.